2021
DOI: 10.3390/socsci10050170
|View full text |Cite
|
Sign up to set email alerts
|

Credibility of Digital Political News in Spain: Comparison between Traditional Media and Social Media

Abstract: In the context of the dissemination of fake news and the traditional media outlets’ loss of centrality, the credibility of digital news emerges as a key factor for today’s democracies. The main goal of this paper was to identify the levels of credibility that Spanish citizens assign to political news in the online environment. A national survey (n = 1669) was designed to assess how the news format affected credibility and likelihood of sharing. Four different news formats were assessed, two of them linked to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
7
1
2
Order By: Relevance
“…In this context, it is important to mention that we examined Instagram representations of traditional news media and compared them to influencers. In contrast, previous research comparing the credibility of traditional media and influencers has mainly focused on traditional media formats, including their traditional layouts, showing that traditional media are considered more credible than SNS in general (i.e., Zimmermann et al, 2020;Besalú and Pont-Sorribes, 2021). We could not find this difference for the SNS representations of traditional media.…”
Section: Effects Of Manipulated Source Expertise On Perceived Source ...contrasting
confidence: 95%
See 1 more Smart Citation
“…In this context, it is important to mention that we examined Instagram representations of traditional news media and compared them to influencers. In contrast, previous research comparing the credibility of traditional media and influencers has mainly focused on traditional media formats, including their traditional layouts, showing that traditional media are considered more credible than SNS in general (i.e., Zimmermann et al, 2020;Besalú and Pont-Sorribes, 2021). We could not find this difference for the SNS representations of traditional media.…”
Section: Effects Of Manipulated Source Expertise On Perceived Source ...contrasting
confidence: 95%
“…In addition, news articles shared by news organizations were perceived as more credible than the same articles shared by their SNS friends ( Tandoc, 2019 ). Besalú and Pont-Sorribes (2021) also found that news presented in a traditional news format (digital newspaper and digital television) was perceived as more credible than the same news presented in a SNS format (Facebook and WhatsApp). Importantly, this also led to higher willingness to share the news presented in the more traditional format.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The importance of credible sources is also evident in inoculation theory, which suggests source effects are key for successful inoculation messages (Compton & Pfau, 2005). This suggests that different sources (e.g., online news media vs news on social media), which are known to differ in perceived source credibility (Besalú & Pont-Sorribes, 2021), may influence the effectiveness of inoculation. In the current research, we develop a warning system that includes expert sources (i.e., findings from scientific research) and consider source effects by assessing the warning with both online news articles and news on social media.…”
Section: Developing the Polarizing Content Warningmentioning
confidence: 98%
“…Advancements in inoculation theory suggest that it is important to consider the source of these messages (for review see Compton & Pfau, 2005), arguably because factors like source trust and credibility are essential for whether warnings of threats and counter arguments against threats are persuasive (see Compton et al, 2021a for discussion). Importantly, though few have examined the effect of sources on inoculation effectiveness (Compton et al, 2021a), some research suggests the effectiveness of inoculation interventions is dependent on source credibility (Traberg & van der Linden, 2022) and that source credibility may be lower for news on social media as compared to traditional online news media (Besalú & Pont-Sorribes, 2021), making it imperative to examine the effectiveness of inoculation warnings from both news and social media sources.…”
Section: Studymentioning
confidence: 99%
“…Its importance increases given the current scenario characterized by the dissemination of fake news and the loss of centrality of traditional media outlets. Besalú and Pont-Sorribes (2021) dedicate their article to analyzing the levels of credibility that Spanish citizens assign to political journalism in the online environment. To achieve this goal, they used a survey (n = 1669).…”
Section: Special Issue Contributionsmentioning
confidence: 99%